Implementation of Integrative Arabic Grammar (Nahwu & Sharaf) Curriculum in Islamic Boarding School - Ade Arip Ardiansyah; Azhar Muhammad (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
Learning Nahwu & Sharaf is considered a frightening subject by students in Islamic boarding schools and informal Islamic boarding schools. One of the reasons is that the institution's existing curriculum has not been planned and presented correctly. One of the institutions with an integrative curriculum to teach Nahwu & Sharaf subjects considered acceptable is the Darul Uluum Islamic Boarding School.This study aimed to describe Nahwu & Sharaf curriculum development concepts and models at Daarul Uluum Islamic boarding school at Majalengka supporting and inhibiting implementing the curriculum. The method used in this study was qualitative research. Data collection used interviews, the teacher's approach to teaching Nahwu & Sharaf, and the Islamic boarding school syllabus.The results showed that Nahwu & Sharaf curriculum development model was a central de-central, which combined two administrative approaches and the grassroots approach. The supporting factors were: 1) Motivation of leaders of Islamic boarding school; 2) Commitments of leaders of Islamic boarding schoolto develop curriculum, 3) Professional competence of Nahwu & Sharaf teachers, and 4) Input of students who have an initial understanding of the material to be obtainable. The inhibiting factors were: 1) the lack of individual funding allocations; 2) the teacher has not been able to properly teach students the material in Nahwu & Sharaf syllabus; 3) the unequal ability of teachers to teach in class Nahwu & Sharaf subjects; and 4) students feel bored while studying in class.